2019
DOI: 10.3390/molecules24122272
|View full text |Cite
|
Sign up to set email alerts
|

Symphytum Species: A Comprehensive Review on Chemical Composition, Food Applications and Phytopharmacology

Abstract: Symphytum species belongs to the Boraginaceae family and have been used for centuries for bone breakages, sprains and rheumatism, liver problems, gastritis, ulcers, skin problems, joint pain and contusions, wounds, gout, hematomas and thrombophlebitis. Considering the innumerable potentialities of the Symphytum species and their widespread use in the world, it is extremely important to provide data compiling the available literature to identify the areas of intense research and the main gaps in order to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 128 publications
(170 reference statements)
3
58
0
5
Order By: Relevance
“…Other PAs, echimidine, echimidine N-oxide and lycopsamine Noxide were obtained at lower detection frequency (less than 30% of the samples) at concentrations of up to 34.7 ng/L. The compounds were previously reported in different Boraginaceae including Symphytum bulbosum, Symphytum o cinale and Symphytum tuberosum (Günthardt et al 2018;Brauchli et al 1982;Brown et al 2016;Salehi et al 2019;Mei et al 2010). This is in agreement with the abundant presence of Symphytum x uplandicum along Ballegab Skovbaek and Vejle rivers.…”
Section: Alkaloidssupporting
confidence: 85%
“…Other PAs, echimidine, echimidine N-oxide and lycopsamine Noxide were obtained at lower detection frequency (less than 30% of the samples) at concentrations of up to 34.7 ng/L. The compounds were previously reported in different Boraginaceae including Symphytum bulbosum, Symphytum o cinale and Symphytum tuberosum (Günthardt et al 2018;Brauchli et al 1982;Brown et al 2016;Salehi et al 2019;Mei et al 2010). This is in agreement with the abundant presence of Symphytum x uplandicum along Ballegab Skovbaek and Vejle rivers.…”
Section: Alkaloidssupporting
confidence: 85%
“…Utilizing toxicological analysis of such secondary metabolites may help in the diagnosis of poisoning or abuse cases. Among the toxic secondary metabolites are harmaline, ibogaine, kawain, cytisine, dimethyltryptamine, harmine, aconitine, atropine, coniine, colchicine, taxine, mescaline, and scopolamine, which are often involved in fatal poisonings [190].…”
Section: Discussionmentioning
confidence: 99%
“…From the root of Dictamnusdasycarpus two antifungal fructoxin alkaloids were isolated. 3-Methoxisampangin ( 78 in Figure 11) of cleistopholispatens showed vast inhibitory activity against each of C. albicans, A. fumigatus, and C. neoformans [190]. Table 4 lists the antifungal activity of the compounds discussed in this section.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Even though the ethnopharmacological studies have shown that various formulations (tinctures, ointments, compresses, and decocts) are ex tempore prepared from fresh roots, generally collected from March to June and from September to October [ 1 , 8 ], dried comfrey roots are commercially available (i.e., in pharmacies, herbal stores) and further processed domestically (in household) or industrially (large-scale) [ 16 ]. However, to the best of our knowledge, there are no previous studies to address the influence of the post-harvest storage time on the chemico-biological potential of S. officinale L.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have already reported a plethora of biological activities of extracts obtained from different Symphytum species (i.e., antimicrobial, antioxidant, anti-inflammatory, wound-healing, anti-nociceptive, anti-enzymatic) [ 3 , 4 , 5 , 7 , 8 , 9 , 10 ]. Furthermore, numerous randomized clinical trials have shown that topical comfrey formulations are able to ameliorate the pain, inflammation, and swelling of muscles and joints from arthritis, bone fractures, contusions, or sprains [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%